(untitled) (Agro Productividad, 2023)
Amaranthus (Amaranthus spp.) is a species of great importance that benefits human and animal nutrition; therefore, its reproduction must be based on useful information obtained from rigorous experiments. Consequently, the aim of this work was to determine the germination of 20 accessions from four Amaranthus spp. The work was carried out at the Instituto Tecnológico de Chiná, Campeche, Mexico, using seeds from Africa, Asia, Greece, South America, the US, and Mexico, donated by The North Central Regional Plant Introduction Station (NCRPIS), Iowa State University. After they were weighed and measured, the seeds were placed in Petri dishes and kept in the dark inside a germination chamber, at 27 ºC and with a 54% relative humidity. Germinated seeds were counted and removed every 24 hours. The analyses were carried out using the ANOVA test in order to identify weight, length, and germination differences between accessions. The results showed no statistical differences in seed length, neither between species nor accessions; however, there were statistical differences in the weight, both between species and between accessions. A. hypochondriacus from India recorded the highest weight (0.00093 ± 0.000075 g). Regarding germination, there were statistical differences between the various evaluation periods (24 and 48 hours): the highest germination was recorded by A. hypochondriacus and A cruentus. Therefore, the following conclusion was reached: seed germination is different between species and accessions.